MARKETING ENDORSEMENT STRATEGY IN BATIK KAMPUS: ISLAMIC BUSINESS ETHICS PERSPECTIVE - Hendri Hermawan Adinugraha (Scientia: Jurnal Hasil Penelitian, 2021)
This research aims to describe the problem of endorsement as a marketing strategy for Batik Kampus Online Shop Buaran Pekalongan from the perspective of Islamic business ethics. The approach used in this research is phenomenology. The research location is in Buaran Pekalongan precisely on Jl. Pelita II, No. 54, Jenggot Gang 4. Sources and data collection techniques in this study using semi-structured interviews, participatory observation, and documentation. Internal validity is done using triangulation, emic and member checking. Data analysis using reduction, display and drawing conclusions. The results of this study concluded that the endorsement marketing strategy carried out by Batik Kampus via Instagram and telegram contained two types of endosers, namely testimonials and celebrity appeal. Endorsement as a Kampus Batik marketing strategy in terms of Islamic Business Ethics as a whole on social media. The products that Batik Kampus promote are not exaggerating and in accordance with Islamic Sharia principles. Products that are traded include products that are polite and cover the body. The use of endorsement as a marketing strategy by Batik Kampus has had a significant positive impact as evidencing by the increased sales turnover and the increase in admins who help him in online business in the market place and proven by the assets owned by Moh. Abdul Ghoni. Kampus Batik services are very fast, friendly and accept dropshipping or packaging which can make it easier for buyers to buy and resell Batik Kampus products to consumers directly.